High thermally stable dielectric permittivity, polarization enhancement and electrostrictive properties in Zr-substituted bismuth sodium titanate lead-free ferroelectric ceramics. Issue 14 (1st October 2020) - Jin, Li; Huang, Yunyao; Pang, Jing; Zhang, Leiyang; Jing, Ruiyi; Guo, Dong; Du, Hongliang; Wei, Xiaoyong; Xu, Zhuo; Lu, Xu; Wei, Fangbin; Liu, Gang
Abstract: Zr-substituted (Bi0.5 Na0.5 )(Ti1− x Zr x )O3 (BNTZ) with x = 0.02–0.4 ceramics were prepared using solid-state reaction technique and their structural, dielectric and ferroelectric properties were investigated systematically. X-ray diffraction results suggest that Zr 4+ ion can enter the (Bi0.5 Na0.5 )TiO3 (BNT) crystal lattices at a limited value and a secondary phase appears in BNTZ ceramics when the x exceeds 0.1. Temperature-dependent dielectric permittivities of BNTZ ceramics show only one dielectric peak from room temperature to 500 °C for each composition, and this dielectric peak becomes broad gradually as x increases from 0.02 to 0.4. The permittivity of x = 0.4 varies less than ±10% between room temperature and 300 °C, indicating a superior thermal stability of the permittivity. Polarization enhancement is revealed by the polarization-electric field hysteresis loops and highest ferroelectric properties are obtained in x = 0.04. The electric-field-induced strains of x = 0.04 show a monotonous increase as temperature increases from 30 °C to 150 °C. At 80 kV/cm, a high strain level of 0.268% is achieved. Our results suggest that the introduction of Zr 4+ ion could effectively tailor the dielectric and ferroelectric properties of BNT ceramics and x = 0.4 composition could find potential application in high temperature capacitor devices.